Effectiveness of a blended care programme for the discontinuation of benzodiazepine use for sleeping problems in primary care: study protocol of a cluster randomised trial, the Big Bird trial. Issue 2 (18th February 2020) - Coteur, Kristien; Van Nuland, Marc; Vanmeerbeek, Marc; Henrard, Gilles; Anthierens, Sibyl; Van den Broeck, Kris; De Sutter, An; Creupelandt, Hanne; Devroey, Dirk; Van Overmeire, Roel; Offermans, Anne-Marie; Kacenelenbogen, Nadine; et al.
Abstract : Introduction: Problematic benzodiazepine use is a global health issue. Although the adverse side effects of long-term use of benzodiazepines are well known, it remains difficult to implement interventions for discontinuation in primary care. Considering the success of blended care for the treatment of sleeping disorders and the support of substance use disorders, evidence suggests that a blended care approach, combining face-to-face consultations with the general practitioner with web-based self-learning by the patient, is beneficial for the discontinuation of chronic benzodiazepine use for primary insomnia in general practice. Therefore, the aim of this study is to evaluate the effectiveness of such an approach for the discontinuation of benzodiazepine and zolpidem, zopiclone and zaleplon drugs ((z-)BZD) use in the long term and evaluate the implementation process. Methods and analysis: This study is a multicentre, pragmatic, cluster randomised controlled trial with 1200 patients, included by 120 general practitioners. Allocation to usual or blended care happens at the level of the general practice in a 1:1 ratio using a block randomisation system stratified per language. The study population consists of adult primary care patients who have been using (z-)BZD for primary insomnia on a daily basis for at least 6 months. Primary outcome measure is the proportion of patients that discontinued (z-)BZD at 12 months assessed by toxicological screening for (z-)BZD in urine. Secondary outcomes include discontinuation of (z-)BZD at 6 months, quality of life and the number of defined daily doses of (z-)BZD prescribed. Data will be collected using a study-specific online platform and analysed using the intention-to-treat approach. The process of implementing blended care will be evaluated in a nested study. Ethics and dissemination: This trial was approved by the Ethics Committee for Research of UZ/KU Leuven (ref. S61194). Study results will be disseminated via open-access, peer-reviewed publications and conference presentations. Trial registration number: NCT03937180 .